Hierarchically Porous Co−N−C Cathode Catalyst Layers for Anion Exchange Membrane Fuel Cells. Issue 18 (13th August 2019) - Zhang, Junfeng; Zhu, Weikang; Pei, Yabiao; Liu, Yang; Qin, Yanzhou; Zhang, Xiangwen; Wang, Qingfa; Yin, Yan; Guiver, Michael D.
Abstract: As a new class of metal–nitrogen–carbon (M−N−C) material with 3 D microstructure, zeolitic imidazolate frameworks (ZIFs) are used to synthesize highly active electrocatalysts for the oxygen reduction reaction, as substitutes for commercial Pt/C in anion exchange membrane fuel cells. However, to form an effective catalyst layer (CL), the relationship between the microstructure of the ZIF‐derived catalyst and the fuel cell performance must be investigated. In this work, a hierarchically porous CL based on the carbon black (CB)‐controlled synthesis of a Co‐based ZIF (denoted as ZIF‐CB‐700) is constructed to optimize the triple‐phase boundary (TPB) and mass transfer. The power density at 40 °C of ZIF‐CB‐700 (95.4 mW cm −2 ) as cathode catalyst is about 4 times higher than that of the catalyst synthesized in the absence of CB and is comparable to that of the commercial 60 % Pt/C catalyst (112.0 mW cm −2 ). Both online and offline measurements suggest that the morphology and microstructure of the CL is crucial to form an active TPB region, dominating the fuel cell performance rather than only the high catalyst activity. Abstract : Most valuable layer : Zeolitic imidazolate frameworks (ZIFs) are used to synthesize highly active electrocatalysts for the oxygen reduction reaction in anion exchange membrane fuel cells. A hierarchically porous catalyst layer based on the carbon black‐controlled synthesis of a Co‐based ZIF is constructed to optimize the triple‐phase boundary and mass transfer. The resultant catalyst exhibits a power density that is comparable to that of the commercial 60 % Pt/C catalyst